A system study on the plant operations department of Bulusan Electrical Corporation - Lao, Kathryn DJ (Animo Repository, 2013)
The purposed of this thesis is to study the present system of Bulusan Electrical Corporation (BEC) located at Mandaluyong City, Philippine. BEC is a sole-proprietor company with the mission of providing quality electrical enclosures and other fabricated metal products to various construction and electrical projects. In line with this mission is to manufacture the product with their industry expertise and commitment into serving their associates, business partners, and the environment. The study is mainly concerned with the production of the mass-produced products, namely, pull boxes, panel boards, and cable trays. The objective of the writers is to identify problems experienced by the company in order to provide them with solutions that would help them to improve their system and to achieve their goals. The problem identified is stated as: Bulusan Electrical Corporation is unable to meet an average percentage of 11.03% of the monthly target output by only using regular working hours, incurring an additional cost of Php 1,049,577.27 in 2012. Critical causes were identified, verified, and validated to contribute to the occurrence of the problem, specifically: Absenteeism of the workers (29.16%), Improper Production Planning (22.42%), Wrong Material Handling (17.86%), Occurrence of Bubbles in the Products (6.33%), Miscommunication between Customer and Accounting Assistant (8.83%), Miscommunication between Customer and Accounting Assistant (*.83), Break Times are not strictly by the Workers (10.00%) and Machine Breakdown (5.41%). The main objective of the study is to eliminate the occurrence of the lost operational hours caused by the stated problem. In order to solve the problem and eliminate 98% of the identified cause, solutions were proposed such as Monthly Ration of Incentives, Planning Ahead of the of Time and Tracking Worker Availability by the Production Head, Job Order Checklist with Standardized unit, Using Platform Trucks and Walkie Stacker for Maternal Handling, Assigning an On-line Quality Control Personnel, Installation of an Alarm Bell and Imposition of strict Break time Policy and In-House Training for the BEC Plant Workers in repairing machines. Cost-benefit Analysis was performed to determine the advantage of implementing the proposed system with BEC. In addition to this, upon the implementation of the proposed system, it is expected to eliminate the Absenteeism of workers, lost operational hours due to Improper Production Planning, Rejects, Reworks, Excessive break times of workers, and Occurrence of machine breakdown. A total of Php 866,673.00 net benefit will be attained upon implementation of the proposed system with a net present value of Php 4,393,341.32 and a payback period of 2.53 months. The duration of the implementation plan will be 77 days.